WORD LEVEL TRANSLATION OF USER MANUAL FOR SAMSUNG GALAXY - Rezqan Noor Farid (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2019)
User manuals are always included in the package of electronic products to make sure the optimality of devices usage. Those manuals are often delivered in English and local languages. This research is intended to measure the equivalence level of translation and also aimed at revealing the strategies of translation used in the manual. The data are taken from the user manuals of Samsung Galaxy Young GTS5360 series Mobile Phone. The manual is printed in two versions: English and Indonesian. Both of themanuals are available online on www.samsung.com. The source language (SL) data are taken from English version, as for the target language (TL) data are taken from Indonesian version. The data consist of 100 various instructions for the users. The analysis of word level equivalence is used to analyse the data. First, the writer took 100 sentences from the sources. Second, the data were then analysed to find words that is not literally equivalent with source language and to analyse the strategies which are used by thetranslator. Third, the writer then gives comments about the naturalness of translations based on the strategies used by the translator. Based on the analysis of data, the writer found that there are five strategies of translation in word level equivalence used by the translator. The strategies are: (1) translation by a more general word (super ordinate), (2) translation using more neutral word / less expressive word, (3) translation by cultural substitution, (4) translation using a loan word, and (5) translation by paraphrase using unrelated words.